A atuação de uma coordenadora pedagógica no Centro de Educação Infantil da SME/SP: cantos e saberes que encantam - Fermi, Raquel Maria Bortone (2017)
The research focuses on the pedagogical coordinator’s work at a Day Care/Childhood Educational Center, in the city of São Paulo. At those educational centers are accepted children from 0 to 3 years old in full time. These children, historical and rightful people, need to be cared, taught, respected and given the opportunities to play, explore and get to know the world. Considering the specificities of the age group, the professionals that work at the Day Care Center shall ensure the children development in a full way. Therefore, the pedagogical work done in this school should favor, good and new experiences. The permanent reflection on the teaching practice and the teacher’s continuing education are indispensable conditions for the fully reach of the goal. In this context, the pedagogical coordinator has a primordial role. They articulate the continued teacher education and the connection of theory and practice. The main goal of this research is to analyze the role of the pedagogical coordinator in the continued teacher education courses, considering the specificities of the children from this age group. The methodological procedures used in this research are: interview, direct observation and document analysis. The data were collected on a Municipal Child’s Educational Center from a Regional Education Direction in the South of São Paulo Regional Direction. The framework of this research included studies by Almeida and Placco (2009), André and Vieira (2010), Almeida (2010), Imbernòn (2009), Oliveira-Formosinho (2007), and Pinazza (2015). Exploring the collected data we can conclude that the coordinator invested and invest in her own education and the teacher’s education based on the established principles of the Pedagogical Political Project from the Day Care. Her performance on the continued education of the teachers, associates practice and theory, without dichotomy, by means of proposals that were meaningful to the group, making possible the collective construction of knowledge and reflection about the teaching practice